Hybrid MQTT–AMQP–SSE Architecture for Efficient Data Delivery in Multi-Sensor IoT Environmental Monitoring: A Topology Comparison Study - Iin Karmila Yusri; Agus Purnawan; Ismail Yusuf Panessai (Jurnal Teknik Informatika (Jutif), 2026)
The rapid growth of the Internet of Things (IoT) has created increasing demands for reliable and efficient data delivery mechanisms in wireless multi-sensor systems, particularly in terms of latency, scalability, and synchronization. This work introduces an efficient data transmission architecture for a wireless multi-sensor monitoring system designed for IoT-based environmental applications. The suggested design incorporates ESP8266-based sensor nodes, RabbitMQ as a message broker, InfluxDB for the storage of time-series data, and a Flask-based web interface for the viewing of real-time data. A hybrid communication protocol integrating MQTT, AMQP, and Server-Sent Events (SSE) ensures rapid data transmission, accurate message queuing, and continuous online streaming availability. We developed and evaluated three network topologies: Star, Tree, and mesh. We employed them to assess latency, throughput, packet loss, and synchronization precision. The Tree topology is optimal, exhibiting a latency of 2 to 4 seconds, ensuring 100% data consistency, and maintaining reliable communication within an 80-meter radius. The RabbitMQ broker exhibits minimal latency (30–272 ms) and has no packet loss, even under high message volume. Wi-Fi mode 802.11 N exhibits superior signal range and stability compared to mode B. The findings indicate that the integration of gateway-based aggregation with a hybrid multi-protocol communication model enhances data reliability and scalability. This provides useful insights for data transfer and distributed data management in IoT monitoring systems based on informatics.